Consumer complaining behavior for local public bus service in İstanbul - Ergüvenç, Ayşe Nilgün Bolcakan. (Thesis (M.A.)- Bogazici University. Institute for Graduate Studies in Social Sciences, 1984., 1984)
This is an exploratory study to examine consumer satisfaction, dissatisfaction and complaining behavior in relation to local public bus service. Reasons for dissatisfactiony levels of dissatisfaction, reasons for not complaining, consumer attitudes toward complaining and toward organizational response to complaints, level of consumer recourse awareness, for public services and complainer attributes were investigated. The study is composed of a literature survey and a field study. The literature survey is composed of a review of services marketing and complaining behavior research in previous areas. The field study was carried out using a sample of 90 members belonging to various bodies at the University of Bosphorous. The sample was given a self administered questionnaire. Frequency analysis and crosstable analysis was made. The major findings were that while the degree of dissatisfaction is very high due mainly to crowded busses, inconsistent bus schedules, and unappropriate number of busses the complaining rate was extremely low. The reason was found to be negative atttidute toward organizational response to complaints. and low recourse awareness. People generally had a positive attitude toward complaining. The research points out the necessity of consumer orientation in public services and that consumer recourse awarenss must be increased.
Keywords: Consumer satisfaction.; Consumer complaints.; Local transit.